Plankton dynamics in a cyclonic eddy in the Southern California Current System. Issue 8 (14th August 2015) - Chenillat, Fanny; Franks, Peter J. S.; Rivière, Pascal; Capet, Xavier; Grima, Nicolas; Blanke, Bruno
Abstract The California Current System is an eastern boundary upwelling system (EBUS) with high biological production along the coast. Oligotrophic offshore waters create cross‐shore gradients of biological and physical properties, which are affected by intense mesoscale eddy activity. The influence of eddies on ecosystem dynamics in EBUS is still in debate. To elucidate the mechanisms that influence the dynamics of ecosystems trapped in eddies, and the relative contribution of horizontal and vertical advection in determining local production, we analyze a particular cyclonic eddy using Lagrangian particle‐tracking analyses of numerical Eulerian. The eddy formed in a coastal upwelling system; coastal waters trapped in the eddy enabled it to leave the upwelling region with high concentrations of plankton and nutrients. The ecosystem was initially driven mainly by recycling of biological material. As the eddy moved offshore, production in its core was enhanced compared to eddy exterior waters through Ekman pumping of nitrate from below the euphotic zone; this Ekman pumping was particularly effective due to the shallow nitracline in the eddy compared to eddy exterior waters. Both eddy trapping and Ekman pumping helped to isolate and maintain the ecosystem productivity in the eddy core. This study shows the importance of cyclonic eddies for biological production in EBUS: they contribute both to the redistribution of the coastal upwelling ecosystem and are local regions of enhanced new production. Together, these processes impact cross‐shore gradients of important biological properties.